1997
DOI: 10.1203/00006450-199711000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of CD4+ and CD8+ T Cells Isolated Immediately ex Vivo Correlates with Disease Severity in Human Immunodeficiency Virus Type 1 Infection

Abstract: Apoptosis of CD4+ and CD8+ T cells has been shown in peripheral blood mononuclear cells (PBMCs) from HIV-infected adults analyzed after overnight culture. Because cell death may be an artifact of in vitro culture, and because there is little information on apoptosis in pediatric HIV disease, we undertook a cross-sectional analysis of apoptosis in PBMCs analyzed immediately ex vivo in HIV-infected children and adults. PBMCs from 22 children, four adolescents, and nine adults and seronegative age-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…Previous studies have demonstrated that CD8 T cells, in addition to CD4 T cells, undergo apoptosis in lymphoid tissue from HIV-infected patients (5,41,42). The conclusion of such studies has been generally that CD8 T-cell death is secondary to their aberrant activation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that CD8 T cells, in addition to CD4 T cells, undergo apoptosis in lymphoid tissue from HIV-infected patients (5,41,42). The conclusion of such studies has been generally that CD8 T-cell death is secondary to their aberrant activation.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 Some studies have also shown a correlation between the extent of apoptosis and disease progression, 7,8 suggesting that, in vivo, HIV kills the CD4 + T cell that it infects. These observations argue that the virus is responsible for the depletion of CD4 + T cells.…”
Section: Apoptosis Of Hiv Infected T Cellsmentioning
confidence: 99%
“…40 Apoptosis is seen in PBL of HIV infected individuals in both the CD4 + and CD8 + T cell subsets. 7,8,40,41 A study of a large cohort of HIV-infected individuals at various stages of disease showed that the degree of apoptosis was significantly higher in CD4 + , CD8 + , and B cells, compared to uninfected individuals, and was correlated with disease progression. 7 This study showed a low level of apoptosis in long-term non-progressors and a high level of apoptosis in rapid progressors.…”
Section: Apoptosis Of Uninfected T Cells: Bystander Cell Deathmentioning
confidence: 99%
“…However in general, progression from acute infection is often accompanied by depletion of the CD4 + lymphocytes and this depletion is a major component of the eventual failure of the immune system and hence AIDS pathogenesis. Apoptosis is one mechanism that contributes to depletion of HIV-1 infected and uninfected cells, deterioration of the immune system and progression to AIDS, respectively (Cotton et al, 1997;Gougeon & Montagnier, 1993;Herbein et al, 1998;Joshi et al, 2011;C. J. Li et al, 1995;Zhu et al, 2011).…”
Section: Point Mutations Associated With Hiv-1 Tropism Transmission mentioning
confidence: 99%